Early Outcomes of Elective Anterior Cervical Diskectomy and Fusion for Degenerative Spine Disease Correlate With the Specialty of the Surgeon Performing the Procedure. Issue 1 (January 2022) - Alomari, Safwan; Judy, Brendan; Weingart, Jon; Lo, Sheng-Fu L.; Sciubba, Daniel M.; Theodore, Nicholas; Witham, Timothy; Bydon, Ali
Abstract : BACKGROUND: Comparative effectiveness research has a vital role in recent health reform and policies. Specialty training is one of these provider-side variables, and surgeons who were trained in different specialties may have different outcomes on performing the same procedure. OBJECTIVE: To investigate the impact of spine surgeon specialty (neurosurgery vs orthopedic surgery) on early perioperative outcome measures of elective anterior cervical diskectomy and fusion (ACDF) for degenerative spine diseases. METHODS: This was a retrospective, 1:1 propensity score-matched cohort study. In total, 21 211 patients were reviewed from the American College of Surgeons National Surgical Quality Improvement Program database. Propensity score matching and subgroup analysis were performed. RESULTS: In both groups (single-level/multilevel ACDF), patients operated on by neurosurgeons had longer operation time (133 vs 104 min/164 vs 138 min), shorter total hospital stay (24 vs 41 h/25 vs 46 h), and lower rates of return to operating room (0.7% vs 2.1%/0.6% vs 2.4%), nonhome discharge (1.2% vs 4.6%/1.0% vs 4.9%), discharge after postoperative day 1 (6.7% vs 11.9%/10.1% vs 18.9%), perioperative blood transfusion (0.4% vs 2.1%/0.6% vs 3.1%), and sepsis (0.2% vs 0.7%/0.1% vs 0.7%; P < .05). In the single-level ACDF group, patients operated on by neurosurgeons had lower readmission (1.9% vs 4.1%) and unplanned intubation rates (0.1% vs 1.1%; P < .05). Other outcome measures and mortality rates were similar among the 2 cohorts in both groups. CONCLUSION: Our analysis found significant differences in early perioperative outcomes of patients undergoing ACDF by neurosurgeons and orthopedic surgeons. These differences might have significant clinical and cost implications for patients, physicians, program directors, payers, and health systems.